HUMAN APPROACH IN THE IMPLEMENTING HEALTH PROTOCOLS FOR WORKERS SAFETY IN THE ENGINEERING OF OIL AND GAS INDUSTRY DURING THE PANDEMIC COVID 19 - Rohmah, Ichmi Yani Arinda; Cahyani, Diva Delinda (Journal of Social Political Sciences, 2022)
The safety of workers in the oil and gas industry during the COVID-19 pandemic has become a serious public concern. It is known, the oil and gas industry is one of the sectors with a large number of workers who are positively infected with the Covid 19 virus. This has led to the implementation of several pillars of work safety for oil and gas industry workers. One of these pillars is the human approach. The human approach in implementing health protocols has a fairly effective role, especially for the safety of workers in operational systems or industrial engineering. A literature review that focuses on several important points, namely: (1) how is the safety of workers in the oil and gas industry engineering sector during the covid 19 pandemic? (2) What is the function of the human approach pillar in the application of worker safety health protocols in the oil and gas industry engineering sector during the COVID-19 pandemic? Several aspects must be considered in the engineering section of the oil and gas industry by identifying installations and equipment, safe work practices, change management, integrated management, environmental management, industrial health and hygiene, contractor management, operations management, and others. While the pillars of the human approach that are of concern in implementing the health protocol are coaching and training, work competence, supervision, ergonomics, building awareness and interaction in the fields of health, work safety, building a safety culture, and building safe behavior at work.